Early Cretaceous arc magmatism and high-sulphidation epithermal porphyry Cu-Au mineralization in Yanbian area, Northeast China: the Duhuangling example - Chai, Peng; Sun, Jing-Gui; Xing, Shu-Wen; Men, Lan-Jing; Han, Ji-Long (International geology review, 2015)
Yanbian area (Northeast China) is part of the Western Pacific porphyry-epithermal gold-copper metallogenic belt. Here, we present the results of a detailed study of Early Cretaceous mineralization-associated magmatic events in this region and, based on the results, identify the geological setting and mineralizing processes involved in mineral deposit formation. We focus on the timing and geodynamic mechanisms of hydrothermal alteration and metallogenesis of the Duhuangling high-sulphidation epithermal gold deposit, located ~15 km NW of the large Xiaoxinancha gold-rich porphyry copper deposit. New data are presented for zircon U-Pb, fluid inclusion Ar-Ar, whole-rock geochemical, and in situ zircon Hf isotopes for igneous rocks of the Duhuangling deposit, and the data - integrated with results of previous research - reveal that Yanbian area epithermal and porphyry Cu-Au deposits are associated with two stages of Early Cretaceous intermediate-felsic magmatism (116-118 and 112-109 Ma), with the later stage of magmatism more closely associated with mineral deposit formation. Our new data constrain the timing of formation of high-sulphidation epithermal gold deposits to 108-106 Ma and the timing of formation of gold-rich porphyry copper deposits to 111-109 Ma. The two stages of magmatism are associated with magmas derived from different sources, with the first-stage magmas potentially derived from partial melting of a depleted mantle wedge that had been metasomatized by subducted slab-derived fluids or melts; these first magmas are also mixed with material derived from the underplated lower crust. Second-stage magmas were probably generated by partial melting of subducting oceanic slab and some oceanic sediments and the interaction of these magmas with melts derived from the overlying lower crust. Most mineralization in the study area is associated with Cu- and Au-rich post-magmatic hydrothermal fluids that were generated during fractionation of hydrous, sulphur-rich, and high oxygen fugacity adakite-like/adakitic mixed magmas. The formation of both igneous rocks and mineral deposits in the study area occurred in a tectonic setting dominated by Late-Early Cretaceous subduction of the Izanagi or Pacific Plate beneath eastern Asia, indicating that the formation of epithermal and porphyry Cu-Au deposits in the Yanbian area involved subduction-derived fluids, melt modification, partial melting, magma mixing, and crystal fractionation.